Platinum Accumulation and Cancer-Related Fatigue, Correlation With IL-8, TNF-α and Hemocytes - Yuling Zhang; Xiaoting Huang; Shanna Feng; Chen Chen; Dainian Guo; Ling Fang (Frontiers Media S.A., 2021)
Platinum-based chemotherapy drugs cause platinum accumulation and result in cancer-related fatigue (CRF), which is related to immune response through still ambiguous mechanisms. We aimed to explore the correlation between platinum and CRF from the perspective of platinum accumulation. After allowing for complete metabolism of the administered platinum drugs, we collected blood samples from 135 patients who had at least two platinum chemotherapy rounds, correlated the platinum concentration (C-Pt), pro-inflammatory cytokines IL-8 and TNF-α, hematological index with therapeutic effect, adverse reactions and fatigue. The median platinum concentration was higher in patients treated with cisplatin than oxaliplatin (424.0 vs 211.3 μg/L), and the occurrence of fatigue was 64.4% in all subjects. Separately, the incidence and degree of fatigue were 74.1% and 9.5 in the patients with higher platinum concentration compared to 57.1% and 2.0 in the lower group. C-Pt, IL-8 and TNF-α were positively correlated with the degree of CRF, while erythrocyte count and hemoglobin were negatively correlated with the degree of CRF. Mediating effect analysis showed that increased IL-8 concentration mediated 57.4%, while decreased erythrocyte count mediated 24.1% of the C-Pt effect on CRF. Platinum accumulation may involve increasing IL-8, cause inflammation or aggravate anemia, which in combination lead to CRF.